Singularly perturbed periodic and semiperiodic differential operators - Mikhailets, V. A.; Molyboga, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
Qualitative and spectral properties of the form sums$$S_{±}(V) := D^{2m}_{±} + V(x),\quad m ∈ N,$$are studied in the Hilbert space $L_2(0, 1)$. Here, $(D_{+})$ is a periodic differential operator, $(D_{-})$ is a semiperiodic differential operator, $D_{±}: u ↦ −iu′$, and $V(x)$ is an arbitrary 1-periodic complex-valued distribution from the Sobolev spaces $H_{per}^{−mα},\; α ∈ [0, 1]$.